Development of Tyrosine-Based Radiotracer Tc99m-N4-Tyrosine for Breast Cancer Imaging. (5th March 2012) - Kong, Fan-Lin; Ali, Mohammad S.; Rollo, Alex; Smith, Daniel L.; Zhang, Yinhan; Yu, Dong-Fang; Yang, David J.
Abstract : The purpose of this study was to develop an efficient way to synthesizeT c 99 m - O -[3-(1, 4, 8, 11-tetraazabicyclohexadecane)-propyl]-tyrosine (T c 99 m -N4-Tyrosine), a novel amino acid-based radiotracer, and evaluate its potential in breast cancer gamma imaging. Precursor N4-Tyrosine was synthesized using a 5-step procedure, and its total synthesis yield was 38%. It was successfully labeled withT c 99 m with high radiochemical purity (>95%). Cellular uptake ofT c 99 m -N4-Tyrosine was much higher than that ofT c 99 m -N4 and the clinical gold standard 18 F-2-deoxy-2-fluoro-glucose ( 18 F-FDG) in rat breast tumor cells in vitro . Tissue uptake and dosimetry estimation in normal rats revealed thatT c 99 m -N4-Tyrosine could be safely administered to humans. Evaluation in breast tumor-bearing rats showed that althoughT c 99 m -N4-Tyrosine appeared to be inferior to 18 F-FDG in distinguishing breast tumor tissue from chemical-induced inflammatory tissue, it had high tumor-to-muscle uptake ratios and could detect breast tumors clearly by planar scintigraphic imaging.T c 99 m -N4-Tyrosine could thus be a useful radiotracer for use in breast tumor diagnostic imaging.